Clonal Hematopoiesis at the Crossroads of Inflammatory Bowel Diseases and Hematological Malignancies: A Biological Link? - Cumbo, Cosimo; Tarantini, Francesco; Zagaria, Antonella; Anelli, Luisa; Minervini, Crescenzio Francesco; Coccaro, Nicoletta; Tota, Giuseppina; Impera, Luciana; Parciante, Elisa; Conserva, Maria Rosa; Redavid, Immacolata; Carluccio, Paola; et al. (Frontiers in Oncology, 2022)
Inflammatory bowel diseases (IBDs) are a group of chronic conditions of the gastrointestinal tract in which nationwide studies have revealed a higher risk of hematological malignancies (HMs). Clonal hematopoiesis (CH) is a premalignant condition defined by the presence of an acquired somatic mutation characterized by a variant allele frequency (VAF) of ≥2%, in a gene frequently associated with HMs. A growing body of evidence suggests a correlation between inflammation and CH; its occurrence in the context of IBD has been previously demonstrated. With the aim to assess CH possible co-occurrence in patients with an IBD associated with HMs, we performed a targeted next-generation sequencing analysis in a cohort of thirteen patients who were referred to our center with IBD associated with HMs. Eleven (85%) patients showed one or more mutations in CH-associated genes; DNMT3A was the most frequently mutated gene, followed by ASXL1 and JAK2. These results may suggest that the mechanisms at the basis of the inflammatory environment could potentially select for the growth of hematopoietic clones harboring specific mutations. In this context, CH emergence may be boosted by the proinflammatory IBD environment, thus acting as a biological link between IBD and the HM onset. If these data are confirmed, IBD patients screened and positive for CH should undergo a hematologic follow-up to assess the risk of developing HM. Future study will clarify the relationship between these conditions.